CHLAMYDIA TRACHOMATIS IN A SEXUALLY TRANSMITTED DISEASE CLINIC – FOUR YEARS RETROSPECTIVE STUDY (2006- 2009) - Araújo Carvalho, Rodrigo (2016)
Chlamydia trachomatis (Ct) is often responsible for an asymptomatic genital infection and represents a major public health problem when untreated. The authors objective was to determinate the Ct genital infection prevalence in a Sexual transmitted infections (STIs) clinic, and to perform an analysis of different variables. It was a retrospective study of all the patients with a Ct infection, observed in the STIs clinic of the Dermatology and Venereology department of Curry Cabral Hospital, between January 2006 and December 2009. The diagnosis was confirmed by Nucleic acid amplification technique. An infection prevalence of 10,5% was found (81 patients with infection in 771 tested). In the 81 infected patients, statistic differences were found in the medium age between male and female patients (male=28,9 vs female=24,3) p=0,018; in the number of different sexual partners in the last 6 months (men= 3,32 vs female=1,5) p=0,009; and in the time in weeks between the beginning of symptoms and the diagnosis (male=2,65 vs female=6,64) p=0,032. The patients with Human immunodeficiency virus (HIV) co-infection had a superior number of different sexual partners in the last 6 months comparing with the non HIV p=0,003. We concluded that in our patients there were demographic, behavioral and clinical differences between male and female, and between HIV and non HIV. Besides that, the elevated prevalence that was found reinforces the importance of the programs instituted for early diagnosis of Ct infection.